Palliative Care Tailored Towards the Needs of the Poor in India - Lal, Mohan (Indian J Surg Oncol, 2015)
Traditional approaches to palliative care may not meet the unique needs of poor cancer patients in developing countries. Cancer patients treated in India are often unable to make repeat visits to the hospital, pay for drugs, or understand and follow complex treatments. Many are from rural areas and may lack basic financial or social support. Our palliative care clinic has taken a series of innovative first steps towards meeting these unique needs, from providing treatment without complete diagnosis, accelerating through the World Health Organization (WHO) analgesic schedule, systematically simplifying prescriptions, and providing treatment free of charge. This paper describes these first steps, presents an initial evaluation of their impacts, and articulates a number of opportunities for additional improvements.